SHIFT OF NOUN PHRASE FOUND IN BILINGUAL TEXT “TALES FROM DJAKARTA”: SHIFT OF NOUN PHRASE FOUND IN BILINGUAL TEXT “TALES FROM DJAKARTA” - Dewa Made Agustawan; Ririn Tasumbey (Universitas Bali Dwipa, 2022)
This study aims to analyze the shift of noun phrase implemented in bilingual text “Tales from Djakarta” and their translation. This study used the theory that is proposed by Catford (1965) which divided the shift in translation into two major types, which is level shift and category shift. This study used descriptive qualitative method to analyze the data found in the story “Tales from Djakarta”. The analyzed was started with the types of shifts in translation found in the data source. The findings indicate that there are two types of shifts in translation of noun phrase found in the story “Tales from Djakarta”. They are structure shift and category shift.